DAILY RATES DEPOSIT SYSTEM IN COOPERATION WITH PROSPEROUS MS, PT. KONDUR PSA - Hery Susanto; Sahni Damerianta P, SKom., MM Sahni Damerianta P, SKom., MM (Jurnal Sistem Informasi, 1999)
The number of members of cooperatives MS. Substantial Prosperous is one source offunds owned by the cooperative's money. but they are reluctant to keep their moneyin cooperative savings in the bank because the interest is higher. to improve existingservices, needs to make a new service that will satisfy the depositors, that is a dailyinterest savings with basically the same with the bank. because of the need forinformation quickly and accurately, we need a computer-based support system.